Comparison of Brain Drain Perception Between Medical and Non-Medical Undergraduate Students in Lahore: Brain Drain Perception Between Medical and Non-Medical Undergraduate Students - Rashid, Attyia; Tariq, Muhammad Haseeb; Aziz, Muhammad Muaz; Imran, Muhammad Mahad; Ahsan, Muhammad Haseeb; Bilal, Muhammad Ilyas (Pakistan Journal of Health Sciences, 2025)
Brain drain is a serious issue for developing countries like Pakistan. Economic, political, and social determinants influence undergraduate students’ intention to migrate. Objectives: To evaluate the perceptions and trends that would determine the intention of brain drain among medical and non-medical undergraduate students in Lahore. Methods: A stratified sampling strategy selected 300 participants from both medical and non-medical programmes. This cross-sectional study was carried out through a properly structured questionnaire from October 2024 to March 2025. Data were entered and analyzed using SPSS V-26; the Chi-square test and Cramer’s V were applied for group comparisons. Results: A total of 300 undergraduates participated (47% male, 53% female; mean age 20.0 ± 1.4 years), with most in first (48.0%) or second year (29.7%). In general, 83.3% expressed willingness to migrate for foreign employment, while 90.3% cited poor working conditions and 76.7% long working hours as push forces. Employment safety abroad was perceived as better by 91.7% of respondents. Two significant discipline-based associations were observed: political instability was more frequently reported by non-medical students than medical students (16.7% vs. 5.3%, p=0.003, Cramer’s V = 0.17), and lifestyle/safety concerns were also more common among non-medical students (31.3% vs. 20.7%, p=0.03, Cramer’s V = 0.13). Conclusions: Brain drain intentions among medical and non-medical undergraduates are substantial overall, driven by workplace environment, as well as socio-economic factors. These systemic problems have to be resolved to ensure that skilled youth are retained.